Treatment pathways in people with type 2 diabetes mellitus: a nationwide cohort study of new users of metformin monotherapy in New Zealand - Simon Horsburgh; Lianne Parkin; David Barson; Joyce Guo; Jiaxu Zeng (BMJ Open)
Objectives The aims of this study were to describe the following: (1) the time to change of therapy in patients with type 2 diabetes who had initiated metformin monotherapy as first-line treatment and (2) the sequence in which subsequent therapeutic regimens were introduced.Design Cohort study.Setting National study based on linked data from the New Zealand Ministry of Health’s National Collections of health and pharmaceutical dispensing data.Participants People with type 2 diabetes mellitus who initiated metformin monotherapy between 1 January 2006 and 30 September 2014 (n=93 874).Primary outcome measures Cumulative incidence curves were plotted to show the time taken to move from one regimen to another, while sunburst plots were used to illustrate the sequence in which regimens were introduced.Results About 10% and 35% of cohort members had moved to a second regimen 1 year and 5 years, respectively, after initiating metformin monotherapy; the majority received a regimen recommended by New Zealand treatment guidelines (mostly metformin and a sulphonylurea). Of those who started a recommended second regimen, 37% and 67% had moved to a third regimen after 1 and 5 years, respectively; the corresponding proportions for those who started an ‘other’ (not listed as recommended) second regimen were 53% and 75%. Most of those who received a third regimen after a recommended second regimen were dispensed an ‘other’ third regimen. Of those who moved to a third regimen from an ‘other’ second regimen, similar proportions received recommended and ‘other’ third regimens.Conclusions Real-world type 2 diabetes treatment patterns in New Zealand are complex and not always consistent with guidelines.